Nanoscale Positioning of Single‐Photon Emitters in Atomically Thin WSe2. Issue 33 (15th June 2016) - Kern, Johannes; Niehues, Iris; Tonndorf, Philipp; Schmidt, Robert; Wigger, Daniel; Schneider, Robert; Stiehm, Torsten; Michaelis de Vasconcellos, Steffen; Reiter, Doris E.; Kuhn, Tilmann; Bratschitsch, Rudolf
Abstract : Single‐photon emitters in monolayer WSe2 are created at the nanoscale gap between two single‐crystalline gold nanorods. The atomically thin semiconductor conforms to the metal nanostructure and is bent at the position of the gap. The induced strain leads to the formation of a localized potential well inside the gap. Single‐photon emitters are localized there with a precision better than 140 nm.